First Report of Glyptothorax ngapang (Vishwanath & Linthoingambi, 2007) from Nagaland, Northeast India - Shekhumcha Y; Limatemjen (The Bioscan, 2024)
The study documents the first record of Glyptothorax ngapang (Vishwanath & Linthoingambi, 2007) from the Zungki River, Nagaland. Morphological characteristics and morphometric data were analyzed, and identification was confirmed by comparing with known descriptions. The species is diagnosed by oval-shaped tubercles with cornified longitudinal ridges, a yellow-brown body coloration, a thoracic adhesive apparatus opening posteriorly with a median depression, and a well-developed adipose fin. This finding adds to the fish diversity of Nagaland and highlights the importance of the region’s freshwater habitats in sustaining endemic species.